Reaction Of The Top 10 Capitalization Shares in the 2020 Pilpres Event - Rahma Nur Praptiwi; Tri Widjatmaka (Eduvest - Journal of Universal Studies, 2021)
This research is a study that aims to see whether there is empirical evidence of the reaction of the Indonesian capital market to international political events, namely the 2020 US Presidential Election using abnormal return indicators and trading volume activity. The research methodology used is event research. This study uses primary data taken from the first party and researchers get data directly from a questionnaire given to all employees of IT companies in the Special Region of Yogyakarta. The population in this study are stocks that are included in the top 10 capitalization companies in Indonesia. The sampling technique in this study used convinience sampling. The data collection technique in this study used a questionnaire equipped with an answer level as the choice of respondents to answer questions. The data analysis technique used multiple linear regression and the application used SPSS version 22. The results of the paired sample t-test statistical calculation both abnormal return and trading volume activity showed that there was no difference in the average abnormal return and trading volume activity before and after the event.